2018
DOI: 10.1111/cea.13080
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for future research into asthma diagnostic tools: A PANEU consensus exercise from the European asthma research innovation partnership (EARIP)

Abstract: The diagnosis of asthma is currently based on clinical history, physical examination and lung function, and to date, there are no accurate objective tests either to confirm the diagnosis or to discriminate between different types of asthma. This consensus exercise reviews the state of the art in asthma diagnosis to identify opportunities for future investment based on the likelihood of their successful development, potential for widespread adoption and their perceived impact on asthma patients. Using a two-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 184 publications
(326 reference statements)
1
21
0
Order By: Relevance
“…Therefore, it appears logical to use indexes of lung function variability over multiple days as objective tools for confirming the diagnosis of asthma and monitor its severity. 10 In the present study, we confirmed that daily self-administered Even though further validation studies are warranted, these results support the view that FOT may become an accurate and rapid tool to document day-to-day variability of airway obstruction, thus possibly representing an additional diagnostic tool for asthma.…”
Section: F I G U R E 1 Comparison Between Fot Variability (Cvr Insp )supporting
confidence: 85%
“…Therefore, it appears logical to use indexes of lung function variability over multiple days as objective tools for confirming the diagnosis of asthma and monitor its severity. 10 In the present study, we confirmed that daily self-administered Even though further validation studies are warranted, these results support the view that FOT may become an accurate and rapid tool to document day-to-day variability of airway obstruction, thus possibly representing an additional diagnostic tool for asthma.…”
Section: F I G U R E 1 Comparison Between Fot Variability (Cvr Insp )supporting
confidence: 85%
“…[6] The BPT is time consuming, has a risk of triggering asthma attack, and is generally not available in primary care; the BDT has limited value for distinguishing asthma from chronic airway diseases; and variable peak expiratory ow requires good cooperation and adherence. [26][27][28] Conspicuously, the UK National Institute for Health and Care Excellence (NICE) recommends that FeNO, a potential indirect predictor of Th2 airway in ammation in asthma, should be measured in all suspected asthma patients. [29] Our data indicated that the optimal cutoff level for FeNO in the diagnosis of asthma was 38 ppb, in line with the recommendation by Japanese Respiratory Society (JRS), [30] who recommend using a FeNO cutoff value of 35 ppb to diagnose asthma.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Therefore, many guidelines recommend that FeNO should be combined with other objective evidence to identify in ammatory respiratory diseases. [1,26,29,33] B-Eos count, another promising and easy-to-measure biomarker, is more attractive as a means of diagnosing asthma. [6,34] In this study, we found that the optimal diagnostic cutoff level was 203 cells/µl for B-Eos to identify asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns arise from generalizability of questions, absence of a global standard diagnosing system for childhood asthma, and validity of the models. Any efforts aimed at constructing models and predictive indices for asthma should address external validity and meticulously identify predictors that are previously identified risk factors from epidemiological studies to correctly describe and predict future asthma -albeit they are predictors from clinical examinations, questionnaires, lung function tests, or biomarker measurements [148].…”
Section: Attempts At Early Prediction Of (Severe) Asthmamentioning
confidence: 99%